2022
DOI: 10.1002/ps.6881
|View full text |Cite
|
Sign up to set email alerts
|

Visual attraction of the European tarnished plant bug Lygus rugulipennis (Hemiptera: Miridae) to a water trap with LED light in chrysanthemum greenhouses and olfactory attraction to novel compounds in Y‐tube tests

Abstract: BACKGROUND: The European tarnished plant bug Lygus rugulipennis Poppius (Hemiptera: Miridae) can cause several types of damage to crops grown in greenhouses and fields, including flower abortion in eggplant, stem and fruit damage in cucumbers, and splits in chrysanthemums. Studies suggest that both male and female L. rugulipennis may be more attracted to traps based on visual attraction than pheromone-based trap. Therefore, the aim of this study was to evaluate the effectiveness of a water trap with LED lights… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
3
0
1
Order By: Relevance
“…Light-emitting diodes (LEDs) have also been used to attract Lygus species to traps in the dark, although it is not clear how this compares with attraction to colored cards studied here. Van Tol et al 33 showed L. rugulipennis were attracted to LEDs emitting in the UV-A/violet wavelengths in a laboratory bioassay, whereas more bugs were caught in water traps baited with white LEDs rather than UV-A LEDs in a greenhouse test. Pan et al 34 reported that green LEDs were most effective in attracting Apolygus lucorum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Light-emitting diodes (LEDs) have also been used to attract Lygus species to traps in the dark, although it is not clear how this compares with attraction to colored cards studied here. Van Tol et al 33 showed L. rugulipennis were attracted to LEDs emitting in the UV-A/violet wavelengths in a laboratory bioassay, whereas more bugs were caught in water traps baited with white LEDs rather than UV-A LEDs in a greenhouse test. Pan et al 34 reported that green LEDs were most effective in attracting Apolygus lucorum.…”
Section: Discussionmentioning
confidence: 99%
“…It would also be useful to increase catches of female bugs on the traps by addition of host-plant volatiles, for example, as has been done for other species of Lygus. 33,[44][45][46]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Польові клопи шкодять також квітково-декоративним рослинам: фуксіям, гортензіям, хризантемам, айстрам (Van Tol et al, 2022).…”
unclassified